Cavity-use and spatial ecology of the Eurasian pygmy owl in the managed boreal forests - Baroni, Daniele (fi=Turun yliopisto|en=University of Turku|, 2022)
The loss and degradation of boreal old-growth forest is threatening biodiversity and a wide range of ecosystem services. Especially in Europe, the boreal forest has been subject to intensification of forestry practices, leading to habitat alteration and loss of nesting site for many taxa. This threat has strongly affected secondary cavity nesters, and many of them are declining among forest birds in Europe. I investigated cavity-use and spatial ecology of a forest-dwelling predator occurring at low densities across its distribution range, the Eurasian Pygmy Owl Glaucidium passerinum, which requires tree cavities for both nesting and food hoarding. I first studied the abundance of suitable tree cavities at the landscape level, and examined the preferences of the owls for different cavity characteristics in two experiments and several years of nest-box monitoring data. I thereafter focused on how cavity distribution in space and time may limit their use during and outside of the breeding season. Using long-term data on the use of nest-boxes resembling tree cavities by individually marked pygmy owls, I compared the habitat and the distances among the nest- boxes used during two different seasons. Moreover, as most of the previous information are from nest-box occupancy, estimating the pygmy owl’s true abundance remains a significant challenge. I therefore used passive acoustic monitoring with a large grid of detectors, and examined the habitat of pygmy owl calling sites and estimated their abundance. Finally, I used GPStracking as an essential conservation tool to fill the gaps of knowledge regarding their spatial ecology. For the first time, we used a small archival global positioning system (GPS) tag to identify and characterize breeding territories of the pygmy owl. We obtained 14 individual home ranges for males during the breeding period 2021 in two different study areas at the latitudinal extremes of the species distribution in Europe: 8 males in the boreal forest in Finland, where there is evidence that the species is declining, and 6 males in the Alps in Italy, where it is expanding its range. My results show that natural cavities were scarce in the landscape (ca. 6.5/km2). However, natural cavity abundance per se does not seem to limit the breeding density of this predator, as suggested by a low occupancy rate in natural cavities and nestboxes. Cavities whose characteristics prevent the nest from being reached by predators were clearly preferred, as the owls selected cavities with more than 5 cm width of the front wall and the nests had 15–30 cm of entrance-bottom distance within the cavity. While the number of cavities per se may not limit the nesting of the owls, they may be limited by suitable habitat with abundant food supply around available cavities, or by lack of cavities in suitable habitats. Comparing the habitat and the distances among the nest-boxes used during two different seasons, I found that pygmy owls appear to be more demanding in their requirements for breeding than for food-hoarding habitat, because of the importance of spruce forests as a nesting habitat and nesting sites being farther from houses than food- hoarding sites. Also, I highlight the need of many different cavities within the home range of each individual, as individually marked pygmy owls mainly used different nest-boxes for nesting and food-hoarding, and they also used different nest-boxes in different years. The results of the passive acoustic survey also demonstrated that the pygmy owl can be considered an old-growth forest specialist. Indeed, my results with habitat data at three spatial scales, and for both calling and nesting sites, show that increasing availability of old-growth forests was consistently the most important habitat variable increasing occupancy probability of the pygmy owls in a landscape dominated by managed forests. When I clustered the detections into territories, I estimated a density of pairs or territorial males that was altogether three times the number of pairs breeding in nest-boxes. Considering the number of natural cavities and nest-boxes, we however estimate that nest-boxes were preferred over natural cavities for breeding. From the GPS-tags study, I found that home ranges are bigger than previously estimated with telemetry data, and there is difference between the two study areas, with owls in the alpine forests having smaller home ranges (90% AKDE 1.47 ± 0.28 km²) than in the boreal forest (90% AKDE 3.08 ± 1.48 km²). I also show that pygmy owls are strictly diurnal, being active from sunrise to sunset in southern Europe, and at almost any time of the day in the North, because nights are not completely dark in the northern summer. Pygmy owls performed long hunting trips, travelled more than expected (4.66 ± 1.79 km per day in the boreal forest and 5.93 ± 1.98 in the alpine forests) and spent most of the time inside coniferous forest, strongly avoiding open habitats and forest edges. All my findings are consistent with the hypothesis that pygmy owl can be considered an old-growth forest species, and I provide for the first time insights on habitat selection for the sites used for nesting and food hoarding sites, for advertising and for hunting. It is crucial information for conservation management strategies, as the pygmy owl’s home ranges are large, diverse, and all its essential properties must be protected. Effective conservation strategies for this old-growth forest specialist should also include the maintenance of high-quality habitat that contains suitable cavities, supporting the need for protection of mature and old-growth forests as a whole, and not just of cavity bearing trees alone.

Varpuspöllön pesäkolojen käyttö ja spatiaalinen ekologia boreaalisissa talousmetsissä Boreaalisen vanhan metsän häviäminen ja heikentyminen uhkaa biologista monimuotoisuutta ja laajaa ekosysteemien kirjoa. Erityisesti Euroopassa boreaalinen metsä on kärsinyt metsien voimakkaasta käytöstä, mikä on johtanut elinympäristöjen muuttumiseen ja monien lajien pesimispaikkojen häviämiseen. Tämä muutos on vaikuttanut toissijaisiin kolopesijöihin, ja monet niistä ovat vähenemässä Euroopan metsälintujen keskuudessa. Tutkin alhaisilla tiheyksillä esiintyvän metsässä elävän saalistajan, varpuspöllön (Glaucidium passerinum), pesäkolojen käyttöä ja alueellista ekologiaa. Laji käyttää koloja sekä pesimiseen että ravinnon varastointiin. Tutkin ensin sopivien puunkolojen runsautta maisematasolla ja pöllöjen mieltymyksiä erilaisiin kolojen ominaisuuksiin kahdessa kokeessa ja useiden vuosien pesäpaikan seurantatiedoilla. Tämän jälkeen keskityin siihen, miten kolojen jakautuminen tilassa ja ajassa voi rajoittaa niiden käyttöä lisääntymiskauden aikana ja sen ulkopuolella. Yksilöllisesti merkittyjen varpuspöllöjen puunkoloja muistuttavien pesäpönttöjen käyttöä koskevan pitkän aikavälin tiedon avulla vertasin pönttöjen ympäristöä ja etäisyyksiä kahden eri vuodenajan aikana. Lisäksi, koska suurin osa aiemmista tiedoista on peräisin pönttöjen käytöstä, varpuspöllön todellisen runsaslukuisuuden arvioiminen on edelleen merkittävä haaste. Siksi käytin passiivista akustista seurantaa suurella havaintopaikkamäärällä, ja tutkin varpuspöllöjen soidinlaulupaikkojen elinympäristöä ja arvioin niiden runsauden. Lopuksi käytin GPS-seurantaa olennaisena suojelutyökaluna, jolla voitiin täyttää aukot, jotka liittyvät pöllöjen alueellista ekologiaa koskevaan tietoon. Ensimmäistä kertaa käytimme pientä GPS-paikanninta varpuspöllön elinpiirin tunnistamiseen ja karakterisointiin. Saimme 14 yksilöllistä koiraiden reviiriä lisääntymiskaudella 2021 kahdelle eri tutkimusalueelle lajien levinneisyyden ääripäässä Euroopassa: 8 koirasta Suomen boreaalisessa metsässä, jossa lajin vähenemisestä on näyttöä, ja 6 koirasta Alpeilla Italiassa, jossa se laajentaa levinneisyysaluettaan. Tulokseni osoittavat, että luonnonkolot olivat niukat ympäristössä (n. 6,5/km2). Luonnonkolojen runsaus sinänsä ei kuitenkaan näytä rajoittavan tämän petoeläimen pesimätiheyttä, kuten luonnonkolojen ja pönttöjen alhainen käyttöaste osoittaa. Kolot, joiden ominaisuudet estävät saalistajia pääsemästä pesään, olivat selvästi suositumpia, koska pöllöt valitsivat kolot, joiden etuseinän leveys on yli 5 cm, ja pesien suuauko ja pohjan etäisyys oli 15–30 cm. Vaikka kolojen lukumäärä sinänsä ei välttämättä rajoita pöllöjen pesimistä, niitä saattaa rajoittaa sopiva elinympäristö, jolla on runsaasti ravintoa käytettävissä olevien kolojen ympärillä, tai kolojen puute sopivissa elinympäristöissä. Verrattaessa kahden eri vuodenajan aikana käytettyjen pesäkolojen elinympäristöä ja etäisyyksiä havaitsin, että varpuspöllöt vaikuttavat vaativammilta lisääntymisvaatimuksiltaan kuin ruokavarastoinnin elinympäristövaatimuksiltaan. Kuusimetsät ovat tärkeämpiä pesimisympäristönä ja pesimispaikat kauempana taloista kuin ruokavarastointipaikat. Korostan myös monien erilaisten kolojen tarvetta jokaisen yksilön reviirillä, sillä yksilöllisesti merkityt varpuspöllöt käyttivät pääasiassa eri eri pönttöjä pesintään ja ruokavarastoina, ja eri vuosina myös eri pesäpaikkoja. Passiivisen akustisen kartoituksen tulokset osoittivat myös, että varpuspöllöä voidaan pitää vanhaa metsää suosivana lajina. Tulokseni kolmesta alueellisesta mittakaavasta sekä kutsu- että pesimispaikoista osoittavat, että vanhojen metsien lisääntyvä saatavuus oli jatkuvasti tärkein luontotyyppimuuttuja, joka lisäsi varpuspöllöjen esiintyvyyttä talousmetsien hallitsemassa maisemassa. Kun ryhmittelin havainnot alueiksi, arvioin parien tai reviirillisten koiraiden tiheyden, joka oli yhteensä kolme kertaa pöntöissä lisääntyvien parien määrä. Kun otetaan huomioon luonnonkolojen ja pesäkolojen määrä, arvioimme kuitenkin, että pönttöjä pidettiin parempina lisääntymiseen kuin luonnonkoloja. GPS-tutkimuksen perusteella havaitsin, että reviirit ovat suurempia kuin telemetriatietojen perusteella aiemmin arvioitiin, ja näiden kahden tutkimusalueen välillä on ero: pöllöillä on alppimetsissä pienemmät reviirit (90 % AKDE 1,47 ± 0,28 km²) kuin boreaalisessa metsässä (90 % AKDE 3,08 ± 1,48 km²). Osoitan myös, että varpuspöllöt ovat tiukasti päiväaktiivisia, ne liikkuvat Etelä-Euroopassa auringonnoususta auringonlaskuun ja lähes mihin aikaan päivästä tahansa pohjoisessa, koska yöt eivät ole täysin pimeitä pohjoisen kesäaikaan. Varpuspöllöt tekivät pitkiä saalistusretkiä, liikkuivat odotettua enemmän (4,66 ± 1,79 km päivässä boreaalisessa metsässä ja 5,93 ± 1,98 alppimetsässä). Kaikki havaintoni ovat sopusoinnussa sen hypoteesin kanssa, että varpuspöllöä voidaan pitää vanha metsän lajina, ja esitän ensimmäistä kertaa tuloksia elinympäristöjen valinnasta pesimis- ja ruokavarastointipaikoille, soidinlauluun ja saalistamiseen. Tämä on olennaisen tärkeää luonnonsuojelustrategioiden kannalta, sillä varpuspöllön reviirit ovat laajat ja monipuoliset, ja kaikkia niiden olennaisia ominaisuuksia on suojeltava. Tämän vanhoja metsiä suosivan lajin tehokkaisiin suojelustrategioihin olisi kuuluttava myös laadukkaiden elinympäristöjen säilyttäminen, joissa on sopivia koloja, ja joilla tuetaan varttuneiden ja vanhojen